Flexible Recruitment of Balance Mechanisms to Environmental Constraints During Walking - Fettrow, Tyler; DiBianca, Stephen; Vanderlinde dos Santos, Fernando; Reimann, Hendrik; Jeka, John (Frontiers in Virtual Reality, 2020)
Background: Humans need to actively control their upright posture during walking to avoid loss of balance. We do not have a comprehensive theory for how humans regulate balance during walking, especially in complex environments. The nervous system must process many aspects of the environment to produce an appropriate motor output in order to maintain balance on two legs. We have previously identified three balance mechanisms that young healthy adults use to maintain balance while walking: 1) The ankle roll mechanism, a modulation of ankle inversion/eversion; 2) The foot placement mechanism, a shift of the swing foot placement; and 3) The push-off mechanism, a modulation of the ankle plantar flexion angle during double stance. We know that these mechanisms are inter dependent and can be influenced by internal factors such as the phase of the gait cycle and walking cadence. Here we seek to determine whether there are changes in neural control of balance when walking in the presence of environmental constraints. Methods: Subjects walked on a self-paced treadmill while immersed in a virtual environment that provides three different colored pathways. Subjects were instructed not to step in the No-Step Zone, which appeared either on the right or left side of the subject. While walking, subjects received balance perturbations in the form of galvanic vestibular stimulation,providing the sensation of falling sideways, either toward the No-Step zone or toward the Neutral zone on the other side. Results: The results indicate that the use of the balance mechanisms are altered depending on whether the perceived fall is toward the No-Step or the Neutral zone. Participants increased the use of the lateral ankle and foot placement mechanisms for No-Step stimuli resulting in a larger shift of the center of mass (CoM) compared to the Neutral stimuli. Conclusion:This experiment provides further evidence that the balance control system during walking is extremely flexible, recruiting multiple mechanisms at different times in the gait cycle to adapt to environmental constraints.